Hubungan Gaya Kepemimpinan Kepala Sekolah Dengan Kompetensi Guru Dalam Mengajar di Taman Kanak-Kanak Kecamatan Lembah Melintang - Mardhotillah, Mardhotillah; Zulminiati, Zulminiati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study was motivated by the efforts of school principals to improve the pedagogical competence of kindergarten teachers in Lembah Melintang Subdistrict, which have not yet reached optimal results. In the classroom, some teachers were found using mobile phones while teaching or relying on them due to a lack of mastery of teaching materials. This research employed a quantitative approach with a correlational method to examine the relationship between the democratic leadership style of school principals and the pedagogical competence of teachers in kindergarten. The subjects consisted of all principals and teachers at kindergartens in Lembah Melintang Subdistrict. The results showed a positive and significant correlation between the democratic leadership style of school principals and teachers’ pedagogical competence, with a significance value of 0.000 < 0.05. This indicates a strong relationship: the higher the level of democratic leadership, the higher the teachers’ pedagogical competence, and vice versa. These findings highlight the importance of democratic leadership in enhancing teachers’ pedagogical competence through participation, support, and a collaborative and professional working environment.